2008
DOI: 10.1103/physrevlett.100.107602
|View full text |Cite
|
Sign up to set email alerts
|

Rashba Effect in the Graphene/Ni(111) System

Abstract: We report on angle-resolved photoemission studies of the electronic pi states of high-quality epitaxial graphene layers on a Ni(111) surface. In this system the electron binding energy of the pi states shows a strong dependence on the magnetization reversal of the Ni film. The observed extraordinarily large energy shift up to 225 meV of the graphene-derived pi band peak position for opposite magnetization directions is attributed to a manifestation of the Rashba interaction between spin-polarized electrons in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
396
2
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(433 citation statements)
references
References 28 publications
31
396
2
4
Order By: Relevance
“…However, the quality of EG still needs to be improved and the effects of the substrate on its properties are not well understood. In addition to the above methods, a number of studies have also reported the growth of graphene on metal substrates, such as ruthenium [32] and nickel [33], but these methods require the sample to be transferred to insulating substrates in order to make useful devices. There are also liquid phase exfoliation approaches to make graphene sheet fi lms by dispersion and exfoliation of graphite in organic solvents [13,34].…”
Section: Preparation Of Graphenementioning
confidence: 99%
“…However, the quality of EG still needs to be improved and the effects of the substrate on its properties are not well understood. In addition to the above methods, a number of studies have also reported the growth of graphene on metal substrates, such as ruthenium [32] and nickel [33], but these methods require the sample to be transferred to insulating substrates in order to make useful devices. There are also liquid phase exfoliation approaches to make graphene sheet fi lms by dispersion and exfoliation of graphite in organic solvents [13,34].…”
Section: Preparation Of Graphenementioning
confidence: 99%
“…12 Finally t r is the strength of Rashba spinorbit coupling that has been shown to be fairly strong. 18 …”
Section: A Three Model Hamiltonianmentioning
confidence: 99%
“…This could happen in a bilayer in contact with a strong SOC metal [31], or in a bilayer where heavy atoms or molecules have been deposited on top of one of the two layers [32].…”
Section: Spin-orbit Proximity Effectmentioning
confidence: 99%